Gergelim irrigado em função da adubação nitrogenada em duas safras agrícolas - Santos, Manoel Galdino dos (Universidade Federal Rural do Semi-Árido, 2017)
Sesame is an oleaginous that presents great economic potential, due to the possibilities of exploration. It is a crop of low productivity, and may be superior when management in fertilization is appropriate. However, more information about the nutrition of the crop is needed. Nitrogen is one of the nutrients that most limits the production of sesame because it is responsible for important functions of metabolism and nutrition of the crop. Therefore, the objective of this work was to evaluate the cultivars of irrigated sesame in the function of nitrogen fertilization in two agricultural crops. Experiments were conducted at the Experimental Farm Rafael Fernandes, belonging to the Federal Rural Semi-Arid University, Mossoró-RN, from February to May (1st crop) and July to October (2nd crop) in 2016. The experimental design was in randomized complete blocks with four replications in a subdivided plots scheme, being allocated in the plots five nitrogen doses (0, 30, 60, 90 and 120 kg ha-1), and the four sesame cultivars in the subplots (CNPA G2 , CNPA G3, CNPA G4 and BRS Silk). The variables evaluated were: nitrogen content in the leaf diagnosis, plant height, stem diameter, number of leaves and capsules, dry mass (leaf, stem, capsules and plants), seed productivity, agronomic efficiency, oil and protein content. The dose of 120 kg ha-1 of nitrogen provided the best agronomic performance for sesame. The cultivar CNPA G4 had the highest productive performance. The cultivar BRS Silk had a higher oil content. The second crop provided better agronomic performance to the sesame crop
Sesame irrigated due to nitrogen fertilization in two agricultural crops
Keywords: Sesamum indicum; Cultivar; Oleaginosa; Época de cultivo; Produtividade de sementes; Sesamum indicum; Grow crops; Oleaginous; Growing season; Seed productivity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA